Preoperative Chemoprophylaxis is Safe in Major Oncology Operations and Effective at Preventing Venous Thromboembolism - Selby, Luke V; Sovel, Mindy; Sjoberg, Daniel D; McSweeney, Margaret; Douglas, Damon; Jones, David R; Scardino, Peter T; Soff, Gerald A; Fabbri, Nicola; Sepkowitz, Kent; Strong, Vivian E; Sarkaria, Inderpal S (Journal of the American College of Surgeons, 2016)
We prospectively evaluated the safety and efficacy of adding preoperative chemoprophylaxis to our institution's operative venous thromboembolism (VTE) prophylaxis policy as part of a physician-led quality improvement initiative. Patients undergoing major cancer surgery between August 2013 and January 2014 were screened according to service-specific eligibility criteria and targeted to receive preoperative VTE chemoprophylaxis. Bleeding, transfusion, and VTE rates were compared with rates of historical controls who had not received preoperative chemoprophylaxis. The 2,058 eligible patients who underwent operation between August 2013 and January 2014 (post-intervention) were compared with a cohort of 4,960 patients operated on between January 2012 and June 2013, who did not receive preoperative VTE chemoprophylaxis (pre-intervention). In total, 71% of patients in the post-intervention group were screened for eligibility; 82% received preoperative anticoagulation. When compared with the pre-intervention group, the post-intervention group had significantly lower transfusion rates (pre- vs post-intervention, 17% vs 14%; difference 3.5%, 95% CI 1.7% to 5%, p = 0.0003) without significant difference in major bleeding (difference 0.3%, 95% CI -0.1% to 0.7%, p = 0.2). Rates of deep venous thrombosis (1.3% vs 0.2%; difference 1.1%, 95% CI 0.7% to 1.4%, p < 0.0001) and pulmonary embolus (1.0% vs 0.4%; difference 0.6%, 95% CI 0.2% to 1%, p = 0.017) were significantly lower in the post-intervention group. In patients undergoing major cancer surgery, institution of a single dose of preoperative chemoprophylaxis, as part of a physician-led quality improvement initiative, did not increase bleeding or blood transfusions and was associated with a significant decrease in VTE rates.